Bibliometric Analysis of Trends and Themes in Human Resource Management Research: A Focus on Indonesian Scholarly Contributions - Sihite, Mislan; Ilham, Rachmad; Purwoko, Bambang; AJi, Lexi Jalu (International Journal of Business, Law, and Education, 2024)
This bibliometric analysis explores trends and themes in Human Resource Management (HRM) research, focusing specifically on contributions from Indonesian scholars. Through systematic data collection and analysis utilizing electronic databases and specialized software, prevalent topics, research methodologies, and publication trends within Indonesian HRM research were identified. The analysis revealed key clusters of research, including electronic human resource management practices, green HRM, strategic management, and innovation. Additionally, less densely covered research areas were highlighted, indicating potential avenues for further exploration. The findings offer valuable insights for academia, industry, and policymakers, facilitating informed decision-making and promoting the advancement of HRM practices in Indonesia.